Global LNG market: supply-demand and economic analysis. Issue 1 (1st February 2022) - Zou, Qian; Yi, Chenggao; Wang, Keming; Yin, Xiuling; Zhang, Yongwei
Abstract: The transition to clean and low-carbon energy is an irresistible trend globally that drives the scale of trade in the global LNG market to grow continuously. The paper reviews the global LNG trade in 2020 and forecasts the future LNG supply and demand. On this basis, the costs in segments of a LNG project are analysed from the perspective of the LNG industry chain. The feasibility of export from LNG projects and the preferred target markets are determined by calculating the economic index of projects. It is concluded that the possibility of future rebound in oil prices and the demand growth in the incremental market in emerging Asian countries are most likely to determine the capacity scales of new LNG projects around the world and contribute to a dynamic balance in the LNG market in the medium- and longterm. The costs in different segments of the LNG industry chain vary greatly with the availability of resources and markets. The economics of LNG export depend on the demand for LNG imports in end markets, the cost plus in different segments of the industrial chain, and the affordability of end consumers. Through the cost and economic analysis on typical LNG Projects, Qatar is found still the most economical and highly profitable country in the global LNG export market nowadays. Unsatisfactory economic performance is a common reason for delayed investments in many large LNG projects in Australia and other countries.